DBP rs7041 and DHCR7 rs3829251 are Linked to CD4+ Recovery in HIV Patients on Antiretroviral Therapy - Salvador Resino; Salvador Resino; María Ángeles Jiménez-Sousa; María Ángeles Jiménez-Sousa; Julià Blanco; Julià Blanco; Yolanda M. Pacheco; Jorge del Romero; Joaquim Peraire; Joaquim Peraire; Ana Virseda-Berdices; Ana Virseda-Berdices; et al. (Frontiers Media S.A., 2022)
Background: The lack of the recovery of CD4+ T-cells (CD4+ recovery) among immunodeficiency virus (HIV)-infected patients on antiretroviral therapy (ART) is not well known. We aimed to analyze the association between single nucleotide polymorphisms (SNPs) underlying vitamin D metabolism and the CD4+ recovery in naïve HIV-infected patients who started ART with low baseline CD4+.Methods: We conducted a retrospective study in 411 naïve individuals with plasma HIV load >200 copies/mL and CD4+ <200 cells/mm3. During 24 months of follow-up, all patients had plasma HIV load <50 copies/mL. DNA genotyping was performed using the Sequenom MassARRAY platform. The outcome variable was the change in CD4+ during the study.Results: CD4+ recovery was higher in patients carrying DBP rs7041 AA genotype (AA versus CC/AC) and DHCR7 rs3829251 AA genotype (AA versus GG/AG) (p-value < 0.05). DBP rs7041 AA genotype was linked to increase in CD4+ (adjusted arithmetic mean ratio (aAMR) = 1.22; q-value = 0.011), increase in CD4+ ≥P75th [adjusted odds ratio (aOR) = 2.31; q-value = 0.005], slope of CD4+ recovery (aAMR = 1.25; q-value = 0.008), slope of CD4+ recovery ≥ P75th (aOR = 2.55; q-value = 0.005) and achievement of CD4+ ≥500 cells/mm3 (aOR = 1.89; q-value = 0.023). Besides, DHCR7 rs3829251 AA genotype was related to increase in CD4+ (aAMR = 1.43; q-value = 0.031), increase in CD4+ ≥P75th (aOR = 3.92; q-value = 0.030), slope of CD4+ recovery (aAMR = 1.40; q-value = 0.036), slope of CD4+ recovery ≥ P75th (aOR = 3.42; q-value = 0.031) and achievement of CD4+ ≥500 cells/mm3 (aOR = 5.68; q-value = 0.015).Conclusion: In summary, DHCR7 rs3829251 and DBP rs7041 polymorphisms were associated with CD4+ recovery in HIV-infected patients who started cART with low CD4+ T-cell counts.